Transcriptomic and histological responses of African rice (Oryza glaberrima) to Meloidogyne graminicola provide new insights into root-knot nematode resistance in monocots - Petitot, Anne-Sophie; Kyndt, Tina; Haidar, Rana; Dereeper, Alexis; Collin, Myriam; de Almeida Engler, Janice; Gheysen, Godelieve; Fernandez, Diana (Annals of botany, 2017)
The root-knot nematode Meloidogyne graminicola is responsible for production losses in rice ( Oryza sativa ) in Asia and Latin America. The accession TOG5681 of African rice, O. glaberrima , presents improved resistance to several biotic and abiotic factors, including nematodes. The aim of this study was to assess the cytological and molecular mechanisms underlying nematode resistance in this accession. Penetration and development in M. graminicola in TOG5681 and the susceptible O. sativa genotype 'Nipponbare' were compared by microscopic observation of infected roots and histological analysis of galls. In parallel, host molecular responses to M. graminicola were assessed by root transcriptome profiling at 2, 4 and 8 d post-infection (dpi). Specific treatments with hormone inhibitors were conducted in TOG5681 to assess the impact of the jasmonic acid and salicylic acid pathways on nematode penetration and reproduction. Penetration and development of M. graminicola juveniles were reduced in the resistant TOG5681 in comparison with the susceptible accession, with degeneration of giant cells observed in the resistant genotype from 15 dpi onwards. Transcriptome changes were observed as early as 2 dpi, with genes predicted to be involved in defence responses, phenylpropanoid and hormone pathways strongly induced in TOG5681, in contrast to 'Nipponbare'. No specific hormonal pathway could be identified as the major determinant of resistance in the rice-nematode incompatible interaction. Candidate genes proposed as involved in resistance to M. graminicola in TOG5681 were identified based on their expression pattern and quantitative trait locus (QTL) position, including chalcone synthase, isoflavone reductase, phenylalanine ammonia lyase, WRKY62 transcription factor, thionin, stripe rust resistance protein, thaumatins and ATPase3. This study provides a novel set of candidate genes for O. glaberrima resistance to nematodes and highlights the rice- M. graminicola pathosystem as a model to study plant-nematode incompatible interactions.